Serum resistin and lipid profile in primigravida females with and without preeclampsia: an analytical cross-sectional study - Rana, Mehwish; Cheema, Mohsin Ali; khan, Rida Ajmal; Kanwal, Asia; Rana, Arshia Mobeen; Khalid Parvez Lone (Journal of the Pakistan Medical Association, 2023)
Objective: To measure and compare the serum levels of resistin and lipid profile parameters in primigravida females with and without preeclampsia. Method: The analytical cross-sectional study was conducted at the Department of Physiology and Cell Biology, University of Health Sciences, Lahore, Pakistan, from 2018 to 2020, and comprised primigravida females having gestational age 30-36 weeks. Those with preeclampsia constituted group 1, while normotensive females constituted group 2. All the participants were subjected to detailed history and general physical examination. Serum resistin levels were measured by enzyme-linked immunosorbent assay, and lipid profile parameters were measured using the colorimetric method. Data was analysed using SPSS 20. Results: Of the 80 women, 40(50percent) were in group 1 with mean age 23.07±2.10 years and mean gestation age 33.45±2.30 weeks. There were 40(50percent) women in group 2 with mean age 23.02±2.11 years and mean gestational age 34.45±1.75 weeks. Mean serum resistin was significantly higher in group 1 compared to group 2 (p 0.02). Mean levels of lipid parameters were significantly different between the groups (p 0.05). Conclusion: Preeclampsia was found to be associated with higher levels of resistin and lipid parameters compared to normal pregnancy. Keywords: Pre-eclampsia, Resistin, Hypertension, Pregnancy outcome, Primigravida.